Comovimiento y concordancia cíclica del empleo en los estados Mexicanos - Marcelo Delajara (Banco de México, 2010)
– Using various statistical measures we estimate the degree of comovement and cyclical synchronization of formal employment across Mexican states. As a measure of formal employment we use the number of workers with permanent contracts registered at the Instituto Mexicano del Seguro Social in each state between July 1997 and April 2009. We find that Mexican states are highly heterogeneous with respect to the degree of employment comovement and the association between the state and national employment. Only in 11 of the 32 states we find that fluctuations in state employment are highly synchronized between them and with national employment. These states are located in the northern border with the United States, in the center west and in the center of the country. Additionally, we find evidence of employment comovement, albeit much weaker, in 4 states located in the vicinity of Mexico City. In the rest of the states, employment fluctuations are unrelated to national employment or other states' employment fluctuations.
Keywords: E32; R11; R23; 330; employment; cycles; comovement; states; regions; Mexico; Regionale Arbeitslosigkeit; Teilstaat; Mexiko